2009
DOI: 10.1021/bm900044x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure of Cationic Groups in Amphiphilic Polymethacrylates Modulates the Antimicrobial and Hemolytic Activities

Abstract: A library of amphiphilic random copolymers containing cationic and hydrophobic side chains were prepared by copolymerization of amine-functionalized methacrylate monomers with various ratios of an alkyl methacrylate. Primary or tertiary amine groups, or quaternary ammonium groups, were utilized as the source of cationic charge in each copolymer series. The antimicrobial and hemolytic activities of these copolymers are reported, enabling a systematic assessment of the effect different amine groups exert on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
378
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(401 citation statements)
references
References 72 publications
21
378
2
Order By: Relevance
“…The chemical formulation of the amine groups also seems to play a critical role in the polymer-cell interaction, as evidenced by HMDA modified hydrogels, has a higher amount of hemolytic activity compared to other tested hydrogels formulated with differently amine groups. Palermo and Kuroda [47] prepared methacrylate based copolymer contained primary or tertiary amine groups, or quaternary ammonium groups, and were utilized as the source of cationic charge in each copolymer series. Measurements of the bactericidal and hemolytic activities in buffers of pH varying from 6 to 8 showed the impact of polymer ionization on biological activity.…”
Section: Hemolytic Activity Of Hydrogel Filmsmentioning
confidence: 99%
“…The chemical formulation of the amine groups also seems to play a critical role in the polymer-cell interaction, as evidenced by HMDA modified hydrogels, has a higher amount of hemolytic activity compared to other tested hydrogels formulated with differently amine groups. Palermo and Kuroda [47] prepared methacrylate based copolymer contained primary or tertiary amine groups, or quaternary ammonium groups, and were utilized as the source of cationic charge in each copolymer series. Measurements of the bactericidal and hemolytic activities in buffers of pH varying from 6 to 8 showed the impact of polymer ionization on biological activity.…”
Section: Hemolytic Activity Of Hydrogel Filmsmentioning
confidence: 99%
“…15 Amino ethyl methacrylate was usually used as charge generating unit and copolymerized with methacrylates bearing various hydrophobic side chains (methyl, 16 butyl, 17 ethyl, 18 hexyl 18 and phenyl 18 ) (Fig. 3).…”
Section: Poly(methacrylate)smentioning
confidence: 99%
“…If the copolymer was too hydrophobic, selectivity for bacterial cell membranes was lost, leading to increased haemolysis, while an excess of cationic charges resulted in high MIC values, which indicates that the polymers were not able to destabilize the target bacterial cell membrane. 16 In a direct comparison of different side chain length /archit ecture s it was found that more hydrophobic monomers require a higher amount of cationic comonomer in order to be effective/selective, and for methacrylate based polymers, the methyl side chain was identified to achieve the highest selectivity when the amphiphilic balance is matched, 19 which also holds true when tertiary amines are used as a hydrophobic component (dimethylamine vs. diethylamine). 20 It becomes obvious how fragile that balance is when small changes in the backbone architecture (met hacy lami de inste ad of methacylate) require much higher ratios of hydrophobic comonomer to work.…”
Section: Poly(methacrylate)smentioning
confidence: 99%
See 2 more Smart Citations